Cytokine Estimation in Chronic Viral Hepatitis with Autoimmune Impairments - Umida Nabieva; Adolat Ismailova (Intelektual Pustaka Media Utama, 2013)
The pattern of autoimmune impairments was studied in patients with chronic viral hepatitis in association with the level of inflammatory cytokines and interferon status. Study was conducted in groups of patients with various levels of the detected autoantibodies to ssDNA. Autoantibodies to ssDNA were found in 37,7% of patients with HCV. In the group of HCV patients with autoimmune disorders, the levels of the cytokines and interferon levels were considerably higher than those in the group of patients without associated autoimmune diseasesDOI: http://dx.doi.org/10.11591/ijphs.v2i2.2438